Cash Holding or Net Debt : What Matters for Firms' Financial Policies ? Evidence from India - Joshi, Himanshu (Indian Journal of Finance, 2021)
The paper examined the relevance and determinants of cash holding and net debt for firms’ financial policies. The sample was constructed from Eikon database of Thomson Reuters considering 500 largest market capitalization firms listed on the National Stock Exchange of India (NSE). Initially, firm level determinants were examined separately for firms’ cash holding and net debt. Then, four subsamples were formed based on the twofold criterion of firms’ debt level and cash flows. These subsample firms were categorized as financially-constrained firms, no cash hedging firms, growth firms, and declining firms. Firm level determinants for cash holding and net debt were examined separately for all the four subsamples. For the complete sample of the firms, larger number of independent variables demonstrated statistically significant relationship with net debt than cash holding. The results confirmed that for financially constrained firms, net debt was more relevant for firms’ financial policies than cash holding. Negative relationship between firm size and cash holding was ubiquitous, signifying economy of scale for cash holding. Relevance of cash holding and net debt was analogous for declining firms. The findings revealed that growth firms placed relatively more emphasis on net debt ; whereas, no-cash hedging firms gave more weightage to cash holding.